Development of Activated Carbon-Ionic Imprinted Polymer Hybrid System in Water Filter to Remove Arsenic Species from Water - Nurlin, Abu Samah (John Wiley & Sons, Inc., 2025)
Activated carbon-ionic imprinted polymer (AC-IIP) is synthesized for the removal of arsenic from water. The IIP is constructed using allylthiourea (AT) as monomer and arsenic as template. The binding properties of the AC-IIP are characterized and detected using Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES) with parameters including comparison of the packing with IIP and without IIP in continuous flow mode, recyclability study and pH effect. The comparison between packing with IIP and without IIP shows an adsorption percentage of 99% until the third cycle, and then the adsorption efficiency drops during the fourth and fifth cycles. The value of adsorption for packing media with IIP is slightly lower than packing media without IIP which is at 98.6% and 98.9% removal efficiency. The optimum pH is at pH 5 which percentage removal is 99%. The recyclability study proves that the AC-IIP can be recycled up to five times with 99% removal at an acidic condition which is at pH 5. Mild pH shows no impact in the recovery of arsenic species into free solution. As a conclusion, AC-IIP shows a high quality of removal efficiency and sorption capacity loaded. Based on the performance demonstrated, AC-IIP is a promising method for arsenic removal from water.